Determinants of Anemia among Early Adolescent Girls in Kendari City - Irfa Ekasanti; Annis Catur Adi; Mardiyono Yono; Fifi Nirmala G; Muhammad Atoillah Isfandiari (Amerta Nutrition, 2020)
Background: Adolescent girls' anemia is a public health challenge. Anemia has an impact on cognitive abilities to reduce intelligence and results in adolescent achievement is down.Objective: The purpose of this study was to analyze the determinants of anemia in early adolescent girls in Kendari City.Methods: This study used a cross-sectional design with a sample of 97 students. Data on parental characteristics, breakfast habits, nutritional status, menstrual status, and history of infectious diseases were collected by interview using a questionnaire. Data on nutrient intake (iron, protein, vitamin C) obtained through the 2x24 hour recall method then compared to the Indonesian standard (AKG). Hemoglobin level was measured using the EasyTouch heamoglobin meter device. Data analysis was done by chi-square analysis and multiple logistic regression analysis.Results: The results showed 28.9% of adolescent girls had anemia. The results of chi-square analysis obtained that there was a relationship between the incidence of anemia on mother's education (p=0.010,), parental income (p=0.017), iron intake (p=0,000), protein intake (p=0,000), vitamin C intake (p=0.023), breakfast habits (p=0.006), menstrual status (p=0.007) and history of infection diseases  (p=0,000). While the results of multiple logistic regression analysis obtained that there was a relationship between iron intake (p=0.005,OR=3.009), protein intake (p=0.007,OR=2.012), vitamin C intake (p=0.038,OR=1.167), menstrual status (p=0.002,OR=3.181) with anemia.Conclusion: The dominant determinant of anemia in early adolescent girls in Kendari City is menstrual status. It is recommended to intervene in risk factors (mother's education, parental income, iron intake, protein, vitamin C, breakfast habits, menstrual status and history of infectious disease) to reduce the prevalence of anemia among adolescent girls.